1998
DOI: 10.1002/(sici)1097-0185(199811)252:3<418::aid-ar10>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil infiltration and degranulation in normal human tissue

Abstract: Localization of eosinophil granule major basic protein by immunofluores-cence permits recognition of both eosinophil infiltration and degranulation. Over the past decade and a half, our laboratory has shown that eosinophil infiltration and degranulation occur in many diseased tissues in humans; among normal tissues studied as controls, only the gut showed striking eosinophil infiltration and degranulation. Using an indirect immunofluores-cence procedure for the detection of major basic protein, we extended our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
140
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(158 citation statements)
references
References 35 publications
9
140
0
7
Order By: Relevance
“…The IL-5 stimulates and activates eosinophils (Lopez et al, 1988). Eosinophilic accumulation is a common feature of gastrointestinal disorders in human medicine (Rothenberg, 2004) and some categories of canine IBD (Allenspach and Gaschen, 2003), although eosinophilic infiltration can also be found in the normal gastrointestinal tract (Kato et al, 1998). Eosinophils have pleiotropic functions such as the release of preformed secondary granula, cytokines, chemokines, neuropeptides or lipid mediators.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-5 stimulates and activates eosinophils (Lopez et al, 1988). Eosinophilic accumulation is a common feature of gastrointestinal disorders in human medicine (Rothenberg, 2004) and some categories of canine IBD (Allenspach and Gaschen, 2003), although eosinophilic infiltration can also be found in the normal gastrointestinal tract (Kato et al, 1998). Eosinophils have pleiotropic functions such as the release of preformed secondary granula, cytokines, chemokines, neuropeptides or lipid mediators.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Notably, eosinophil infiltrations were only associated with eosinophil degranulation in the GI tract. Examination of eosinophils throughout the GI tract of conventional healthy mice (untreated mice maintained under pathogen-free conditions) has revealed that eosinophils are normally present in the lamina propria of the stomach, small intestine, cecum, and colon.…”
Section: Physiological Presence Of Eosinophils In the Gastrointestinamentioning
confidence: 99%
“…In an autopsy study, low-grade eosinophilic infiltration and degranulation in the gut was observed to occur in normal subjects although eosinophil counting (quantitative histology) was not performed [8]. In the present study by Alhmoud et al [1], the limit applied was [25 eosinophils/HPF in the proximal GI tract and 50/HPF in the colon.…”
mentioning
confidence: 62%